Interpersonal communication as an agent of normative influence: a mixed method study among the urban poor in India - Rimal, Rajiv N. (Reprod Health, 2015)
BACKGROUND: Although social norms are thought to play an important role in couples’ reproductive decisions, only limited theoretical or empirical guidance exists on how the underlying process works. Using the theory of normative social behavior (TNSB), through a mixed-method design, we investigated the role played by injunctive norms and interpersonal discussion in the relationship between descriptive norms and use of modern contraceptive methods among the urban poor in India. METHODS: Data from a household survey (N = 11,811) were used to test the underlying theoretical propositions, and focus group interviews among men and women were then conducted to obtain more in-depth knowledge about decision-making processes related to modern contraceptive use. RESULTS: Spousal influence and interpersonal communication emerged as key factors in decision-making, waning in the later years of marriage, and they also moderated the influence of descriptive norms on behaviors. Norms around contraceptive use, which varied by parity, are rapidly changing with the country’s urbanization and increased access to health information. CONCLUSION: Open interpersonal discussion, community norms, and perspectives are integral in enabling women and couples to use modern family planning to meet their current fertility desires and warrant sensitivity in the design of family planning policy and programs.